The combination of salt and drought benefits selective ion absorption and nutrient use efficiency of halophyte Panicum antidotale - Hussain, Tabassum; Asrar, Hina; Zhang, Wensheng; Liu, Xiaojing (Frontiers in Plant Science, 2023)
Soil salinity and water deficit often occur concurrently, but understanding their combined ‎effects on plants’ ion regulation is limited. We aim to identify if introducing drought with ‎salinity alleviates salt stress’s ionic effects. For this, Panicum antidotale – a halophytic grass- ‎was grown under single and combined stressors, i.e., drought and salt (low and high), and ‎regulation of various cations and anions along with the antioxidant capacity and ‎modifications in leaf anatomy were investigated. Results showed a combination of low salt ‎and drought minimally affected plant (dry) mass by improving the selective ions absorption ‎and nutrient use efficiencies. The lowest ratio for efficiency of photosystem II and carbon ‎assimilation (ΦPSII/ΦCO2) suggested less generation of reactive oxygen species, which were ‎probably detoxified with constitutively performing antioxidant enzymes. In contrast, the ‎combination of high salinity and drought escalated the adverse effects caused due to ‎individual stressors. The selective ion absorption increased, but the non-selective ions ‎transport caused an ionic imbalance, and the highest ratio of Na+/K+ was recorded. Although ‎the area of mesophyll increased, a reduction in epidermal tissues (number and area) predicted ‎a mechanical injury prone to water loss in these plants. The compromised activity of ‎antioxidant enzymes also suggested treatment-induced oxidative damage. Yet, the synergistic ‎interaction between high salinity and drought was not detrimental to the survival of P. ‎antidotale. Therefore, we suggest planting this grass in habitats with harsh environmental ‎conditions to meet the increasing fodder demands without compromising agricultural lands' ‎productivity. ‎